The Effect of ROA, ROE, DER, and DAR on Stock Prices - Dinda Soraya; Daniel Purba; Tiomaida Situmorang; Melisa Jovanka Natasya Girsang; Fuji Astuty; Fanesa Isalia Minanda Syaefudin (International Journal Of Economics Social And Technology, 2023)
The business world is currently undergoing rapid development, evident from the emergence of new companies with competitive advantages. Consequently, intense business competition has arisen, compelling companies to enhance their capabilities in order to survive and compete effectively. Selling shares to the public in the capital market is one of the key factors that support the continuity of an industry. The capital market can be defined as a sector where securities such as stocks, stock certificates, and bonds are traded. In Indonesia, the Indonesia Stock Exchange (IDX) serves as a platform for investors and the industry to converge. Such circumstances directly impact capital market activities, leading to fluctuations in the demand and supply of shares on the stock exchange. Consequently, these fluctuations have a profound effect on share prices, necessitating investors to remain vigilant, particularly in the case of energy companies